Identifying DNA methylation in a nanochannel. Issue 1 (1st December 2016) - Sun, Xiaoyin; Yasui, Takao; Yanagida, Takeshi; Kaji, Noritada; Rahong, Sakon; Kanai, Masaki; Nagashima, Kazuki; Kawai, Tomoji; Baba, Yoshinobu
Abstract: DNA methylation is a stable epigenetic modification, which is well known to be involved in gene expression regulation. In general, however, analyzing DNA methylation requires rather time consuming processes (24–96 h) via DNA replication and protein modification. Here we demonstrate a methodology to analyze DNA methylation at a single DNA molecule level without any protein modifications by measuring the contracted length and relaxation time of DNA within a nanochannel. Our methodology is based on the fact that methylation makes DNA molecules stiffer, resulting in a longer contracted length and a longer relaxation time (a slower contraction rate). The present methodology offers a promising way to identify DNA methylation without any protein modification at a single DNA molecule level within 2 h. Abstract :